Comparative ungulate diversity and biomass change with human use and drought: Implications for community stability and protected area prioritization in African savannas - Bartzke, G.S.; Ogutu, Joseph O.; Piepho, H.P.; Bedelian, C.; Rainy, M.E.; Kruska, R.L.; Worden, J.S.; Kimani, K.; McCartney, M.J.; Ng'ang'a, Leah; Kinoti, J.; Njuguna, E.C.; et al. (Wiley, 2025)
Drought and human use may alter ungulate diversity and biomass in contrasting ways. In African savannas, resource-dependent grazers such as wildebeest (Connochaetes taurinus) and zebra (Equus quagga) may decline or disperse as resources decline, opening space for more drought-tolerant species such as gazelles (Eudorcas and Nanger) and impala (Aepyceros melampus). This shift can increase species richness, evenness, and overall ungulate diversity. Although higher diversity may stabilize ungulate communities, it may be associated with lower biomass (the total body mass of all individuals in a community), which in turn affects vegetation structure and composition, nutrient cycling, energy flows, and other organisms in savannas. While ungulate biomass often declines during drought or in areas of intense human use, the effects on diversity changes under low-to-moderate human use remain less clear. Our fine-scale censuses in the Maasai Mara National Reserve and adjacent pastoral lands in Kenya showed that ungulate biomass declined more than diversity in the 1999 drought year. In the normal rainfall year of 2002, diversity peaked along the reserve boundary, but species richness leveled off in the drought year. Biomass peaked in the reserve in both census years, and migratory ungulates moved further into the reserve in the drought year, where diversity declined. These findings suggest that core protected areas are crucial for maintaining ungulate biomass, while transition zones from protected and pastoral lands support higher diversity unless drought reduces species richness.